2021
DOI: 10.1186/s40900-021-00253-6
|View full text |Cite
|
Sign up to set email alerts
|

The practice of active patient involvement in rare disease research using ICT: experiences and lessons from the RUDY JAPAN project

Abstract: Background The role of patients in medical research is changing, as more emphasis is being placed on patient involvement, and patient reported outcomes are increasingly contributing to clinical decision-making. Information and communication technology provides new opportunities for patients to actively become involved in research. These trends are particularly noticeable in Europe and the US, but less obvious in Japan. The aim of this study was to investigate the practice of active involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…These communication channels are a part of a larger network involving the practitioner community, support groups, funding agencies, and health authorities. Describe PI in the use of different dissemination channels like social media, webpages, etc Did not describe methods for assessing the impacts of PI in research dissemination Described that PI creates more opportunities for research translation when it is closely connected to the patient community affected No description of the effectiveness (cost-benefits) of PI Hamakawa et al [ 13 ] The practice of active patient involvement in rare disease research using ICT: experiences and lessons from the RUDY JAPAN project Research Involvement and Engagement Japan and United Kingdom Mixed method, quantitative questionnaire and web meeting To investigate the practice of active involvement of patients in medical research in Japan by utilizing a digital platform, and to analyze the outcomes to clarify what specific approaches could be put into practice Patients with Skeletal muscle channelopathies and hereditary angioedema The number of participants not described A rare disease research platform that utilizes Information and Communication Technology (ICT) and Steering Committee meetings Several approaches for PI were designed through patient-researcher collaboration, namely the Steering Committee, questionnaire development, dynamic consent, and other communication strategies. Patients were involved in: conceptualizing, governance, software system, questionnaire, recruitment, data use, analyzing and interpretation, communication and dissemination They described that they analyzed the research process of practices and experiences on how each approach of PI affected and contributed to the research project They reported increased self-efficacy for the patients involved and believe patients expertise influence research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These communication channels are a part of a larger network involving the practitioner community, support groups, funding agencies, and health authorities. Describe PI in the use of different dissemination channels like social media, webpages, etc Did not describe methods for assessing the impacts of PI in research dissemination Described that PI creates more opportunities for research translation when it is closely connected to the patient community affected No description of the effectiveness (cost-benefits) of PI Hamakawa et al [ 13 ] The practice of active patient involvement in rare disease research using ICT: experiences and lessons from the RUDY JAPAN project Research Involvement and Engagement Japan and United Kingdom Mixed method, quantitative questionnaire and web meeting To investigate the practice of active involvement of patients in medical research in Japan by utilizing a digital platform, and to analyze the outcomes to clarify what specific approaches could be put into practice Patients with Skeletal muscle channelopathies and hereditary angioedema The number of participants not described A rare disease research platform that utilizes Information and Communication Technology (ICT) and Steering Committee meetings Several approaches for PI were designed through patient-researcher collaboration, namely the Steering Committee, questionnaire development, dynamic consent, and other communication strategies. Patients were involved in: conceptualizing, governance, software system, questionnaire, recruitment, data use, analyzing and interpretation, communication and dissemination They described that they analyzed the research process of practices and experiences on how each approach of PI affected and contributed to the research project They reported increased self-efficacy for the patients involved and believe patients expertise influence research.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 primary articles were all published in English, conducted between 2012 [ 31 ] and 2021 [ 35 ], and originating from USA (n = 4), Europe (n = 4), Oceania (n = 3) and Japan (articles = 1). The studies described PI in research of different types of RDs: neuromuscular diseases [ 32 , 33 ], congenital hypogonadotropic Hypogonadism /Kallmann syndrome [ 11 ], Fontan disease [ 34 ], eosinophilic gastrointestinal disorder [ 35 ], scleroderma disease [ 36 ], vasculitis disease [ 12 ], Pachyonychia Congenita [ 37 ], skeletal muscle channelopathies and hereditary angioedema [ 13 ], and rare disease in general [ 31 , 38 , 39 ]. Both patients, patient representatives and patient organization representatives were involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially beneficial in rare disease research because it is difficult to recruit a sufficient number of participants in geographically limited areas. As clarified by the Rare and Undiagnosed Diseases Study (RUDY) in the United Kingdom and Japan, digital platforms enable the effective recruitment of participants [ 5 - 7 ]. Additionally, the RUDY project demonstrated that digital technologies facilitate dialog and collaboration between patients and researchers [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As clarified by the Rare and Undiagnosed Diseases Study (RUDY) in the United Kingdom and Japan, digital platforms enable the effective recruitment of participants [ 5 - 7 ]. Additionally, the RUDY project demonstrated that digital technologies facilitate dialog and collaboration between patients and researchers [ 5 - 7 ]. This type of active patient involvement encouraged by digital tools is referred to as participant-centric initiatives [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%